(untitled) (Baghdad Science Journal, 2024)
This paper, established the existence and uniqueness of common fixed points for Kannan, Reich, and Chatterjea-type pairs of self-maps in complete b-metric space. In addition, an example and an application of the existence and uniqueness of common solutions for a system of functional equations arising in dynamic programming are discussed by using our results